#TITLE_ALTERNATIVE# - NUR'ALIF (NIM : 12213095), HANIF
In recent years, the phenomenon of low world oil prices has caused instability and threatened the sustainability of oil and gas industry. To survive, efficiency improvements are needed by reducing the cost of lifting the crude oil from the wells. In order to maintain its quality, this cost reduction is not necessary in every stage of the entire oil production system. Therefore, it is necessary to determine the best scenario that can improve the efficiency of each component in the whole system, so that optimal oil acquisition can be achieved as well as can be produced economically. In this study, the optimal oil acquisition is determined based on the results of comprehensive investigation of well production system, including the utilization of artificial lift on Field X using commercial software GAP to maximize oil acquisition while reducing operating costs. GAP is a multiphase oil and gas optimiser tool based on non-linear SQP technique (Sequential Quadratic Programming) in modelling the surface network of the field production system. Oil acquisition optimization using GAP is done based on scenarios that have been arranged in the system so that oil acquisition can be maximized and can be economic. The most economical development scenario in optimizing the oil acquisition of Reservoir 1 of Field X is obtained by optimizing the flow rate of gas lift injection at all wells, increasing the productivity index value on poorly performing wells through workover activity, arranging the X-8 well (not open during simulation), and by adjusting the maximum drawdown pressure on X-6 and X-5 wells of 300 psi, which can generate 10% NPV value of 97.64 MM US$, an increase of 25 MM US$ from base case scenario. As for Reservoir 2 of Field X, the most economical development scenario is obtained by optimizing the flow rate of gas lift injection at the X-12 well, which can generate 10% NPV value of 1.65 MM US$, an increase of 0.5 MM US$ from base case scenario.